Practical experiences in daycare and the development of baby awareness - Irineu Aliprando Tuim Viotto Filho; José Ricardo Silva; Rod Parker-Rees (Universidade do Oeste Paulista, 2023)
The present study was motivated by theoretical findings that indicate that, when working with babies in day care, in general, there are still conceptions that characterize the routine as household chores, focused on protection, food and hygiene, a non-directive teaching job, spontaneous, based on everyday life and waiting for the baby's development to come and that, for this reason, there is no pedagogical work to be done with him. This text aims to defend the pedagogical practices experienced at the daycare as promoters of the baby's awareness development. We understand consciousness as a typically human capacity that develops through social interactions and cultural appropriations since the birth of the baby. This theoretical-bibliographic study is based on historical-cultural theory and its understanding of child development process. This theory has helped us to understand human development from an early age in distinctive periods which each have their leading activities that contribute most to this process. As a result it shows us the necessity of intentional pedagogical practices mediations to provide babies with moments of objects exploration and relationships with more experienced individuals who use speech to signify human actions. Such discussion collaborates with the teacher in his function, who plans and organizes didactic elements in order to enable the baby's development of consciousness in the daycare center.